Popular Stoicism in the Face of Social Uncertainty - Renata Dopierała (Qualitative Sociology Review, 2022)
The article discusses popular Stoicism (a modern, simplified, and often commercialized version of ancient Stoicism), which is offered as an answer to the uncertainty of modernity. The financial, political, climate, and health crises have been detrimental to the sense of agency and control over one’s life, leading individuals to seek ways of (subjectively) regaining it. Popular Stoicism can be viewed as an expert system providing individuals with a specific vision of happiness and the good life, in addition to offering practical knowledge on how to define an area of individual agency by negotiating the boundaries between that which is within one’s power and that which is not. Reflections begin with a juxtaposition of ancient and contemporary Stoicism, focusing on their different socio-cultural origins, followed by a synthesis of the principles of ancient Stoicism on happiness and the good life and a detailed interpretation of the ‘offering’ of popular Stoicism in the relevant areas. In the latter context, two chosen Stoic exercises (necessary to achieve happiness and the good life) are discussed—the ability to recognize what things depend/do not depend on us and Stoic emotion work. The practices and techniques recommended as a part of constant work on oneself are also supposed to teach individuals to adapt to their unstable reality. As a result, the popular version of Stoicism perpetuates the mechanisms of the culture of individualism, which holds the individual fully responsible for their life, and the therapeutic and counseling culture (based on one’s readiness to constantly self-improve), which is a new form of disciplining in a neoliberal society. Both are important elements of the everyday life and lifestyle of the middle class. This class is interested in self-fulfillment and is the primary target audience of contemporary Stoic handbooks. The consideration is based on fragments of books on popular Stoicism, mainly written by Polish philosophers, subjected to qualitative content analysis.